PENGARUH FERMENTASI ONGGOK SINGKONG KOMBINASI TEPUNG DAUN LAMTORO (Leucaena leucocephala) SEBAGAI PAKAN ALTERNATIF TERHADAP PERTUMBUHAN ITIK PEKING (Anas platyrhyncos) SEBAGAI SUMBER BELAJAR BIOLOGI - Mahmud Syafi’i; Achyani Achyani; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
Peking duck (Anas platyrhyncos) is a type of poultry that has high economic value and has many advantages over other livestock. The use of alternative feeds can later increase the weight of Peking ducks and reduce maintenance costs in terms of feed. One of the alternative uses is fermentation of cassava onggok with a combination of lamtoro leaf flour (Leucaena leucocephala). The purpose of this study was to determine the effect of alternative feed for ferrmented onggok combination of lamtoro leaves flour (Leucaena leucocephala) on weight growth of Peking duck (Anas platyrhyncos). This type of research is an experiment using a completely randomized design (CRD) and using 3 treatments, one control and 6 replications. The research was conducted for 45 days from 23 April to 1 June 2020. The parameters observed were the weight gain of Peking duck (Anas platyrhyncos). The data obtained were analyzed using the One Way Anava Test. The results showed that the effect of alternative feed for fermented onggok combination of lamtoro leaves flour (Leucaena leucocephala) had an effect on the weight growth of Peking duck (Anas platyrhyncos). The results of this study can be used as a source of learning biology in the form of Student Worksheet.